2016
DOI: 10.3389/fpls.2016.01192
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Subcellular Metal Homeostasis: The Key to Crop Improvement

Abstract: Iron (Fe), zinc (Zn), manganese (Mn), and copper (Cu) are essential micronutrient mineral elements for living organisms, as they regulate essential cellular processes, such as chlorophyll synthesis and photosynthesis (Fe, Cu, and Mn), respiration (Fe and Cu), and transcription (Zn). The storage and distribution of these minerals in various cellular organelles is strictly regulated to ensure optimal metabolic rates. Alteration of the balance in uptake, distribution, and/or storage of these minerals severely imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 102 publications
(177 reference statements)
0
96
0
2
Order By: Relevance
“…One strategy is efficient Cd chelation followed by vacuolar sequestration (e.g. via phytochelatin binding) or by direct transport into the vacuole, which can be mediated by HMA3 and Cation Exchanger (CAX) 2 and 4 (Bashir et al ., ). Another strategy proposed for both A. thaliana and A. halleri is the activation of antioxidant mechanisms or the prevention of ROS accumulation by CAX1‐mediated cytosolic calcium (Ca) sequestration in vacuoles to avoid the Ca–ROS positive feedback loop (Baliardini et al ., , ).…”
Section: Introductionmentioning
confidence: 99%
“…One strategy is efficient Cd chelation followed by vacuolar sequestration (e.g. via phytochelatin binding) or by direct transport into the vacuole, which can be mediated by HMA3 and Cation Exchanger (CAX) 2 and 4 (Bashir et al ., ). Another strategy proposed for both A. thaliana and A. halleri is the activation of antioxidant mechanisms or the prevention of ROS accumulation by CAX1‐mediated cytosolic calcium (Ca) sequestration in vacuoles to avoid the Ca–ROS positive feedback loop (Baliardini et al ., , ).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that there is cross-talk in mineral uptake and accumulation among the ions, such as between Zn-Fe and As-P (Pineau et al, 2012;LeBlanc et al, 2013). Especially in transport system, molecular mechanism of Cu, Fe, and Zn homeostasis and their interactions, which often include interactions with toxic metals, were releveled in plants (Puig et al, 2007;Bernal et al, 2012;Sinclair and Krämer, 2012;Bashir et al, 2016). These reports suggested that integration of multiple GWAS results targeting various minerals could identify the loci controlling the cross-talk of uptake and accumulation of multiple minerals.…”
Section: Gwas For Mineral Contentmentioning
confidence: 99%
“…27 Moreover, too much or too little of a given metal nutrient in a given location can be detrimental to the living system. 811 …”
mentioning
confidence: 99%